Halal Meets Biotech: Exploring Integration Opportunities and Challenges in Malaysian Universities - Marina Abu Bakar; Afiffudin Mohammed Noor; Syaimak Ismail @ Mat Yusoff (Universiti Sains Islam Malaysia, 2025)
Indexed by MyCite